Metabolic activation of 2‐amino‐1‐methyl‐6‐phenylimidazo [4, 5‐b]pyridine and DNA adduct formation depends on p53: Studies in Trp53(+/+), Trp53(+/−) and Trp53(−/−) mice. Issue 4 (22nd September 2015) - Krais, Annette M.; Speksnijder, Ewoud N.; Melis, Joost P.M.; Singh, Rajinder; Caldwell, Anna; Gamboa da Costa, Gonçalo; Luijten, Mirjam; Phillips, David H.; Arlt, Volker M.
Abstract : The expression of the tumor suppressor p53 can influence the bioactivation of, and DNA damage induced by, the environmental carcinogen benzo[ a ]pyrene, indicating a role for p53 in its cytochrome P450 (CYP)‐mediated biotransformation. The carcinogen 2‐amino‐1‐methyl‐6‐phenylimidazo[4, 5‐ b ]pyridine (PhIP), which is formed during the cooking of food, is also metabolically activated by CYP enzymes, particularly CYP1A2. We investigated the potential role of p53 in PhIP metabolism in vivo by treating Trp53(+/+), Trp53(+/−) and Trp53(−/−) mice with a single oral dose of 50 mg/kg body weight PhIP. N ‐(Deoxyguanosin‐8‐yl)‐2‐amino‐1‐methyl‐6‐phenylimidazo[4, 5‐ b ]pyridine (PhIP‐C8‐dG) levels in DNA, measured by liquid chromatography‐tandem mass spectrometry, were significantly lower in liver, colon, forestomach and glandular stomach of Trp53(−/−) mice compared to Trp53(+/+) mice. Lower PhIP‐DNA adduct levels in the livers of Trp53(−/−) mice correlated with lower Cyp1a2 enzyme activity (measured by methoxyresorufin‐O‐demethylase activity) in these animals. Interestingly, PhIP‐DNA adduct levels were significantly higher in kidney and bladder of Trp53(−/−) mice compared to Trp53(+/+) mice, which was accompanied by higher sulfotransferase (Sult) 1a1 protein levels and increased Sult1a1 enzyme activity (measured by 2‐naphthylsulfate formation from 2‐naphthol) in kidneys of these animals. Our study demonstrates a role for p53 in the metabolism of PhIP in vivo, extending previous results on a novel role for p53 in xenobiotic metabolism. Our results also indicate that the impact of p53 on PhIP biotransformation is tissue‐dependent and that in addition to Cyp1a enzymes, Sult1a1 can contribute to PhIP‐DNA adduct formation. Abstract : What's new? Many environmental carcinogens must be metabolized to form reactive electrophilic species capable of damaging DNA. The tumour suppressor p53 was shown to influence the cytochrome P450 (CYP)‐mediated biotransformation of the environmental carcinogen benzo[ a ]pyrene. The suspected carcinogen 2‐amino‐1‐methyl‐6‐phenylimidazo[4, 5‐ b ]pyridine (PhIP), which is formed during the cooking of food, is also metabolically activated by CYP enzymes. This study shows that expression of p53 influences the biotransformation of PhIP. Using a gene knockout mouse model, the authors show that the impact of p53 on PhIP‐DNA adduct formation is tissue‐dependent and that, in addition to cytochrome P450 enzymes, sulfotransferases contribute to the bioactivation of PhIP.